SUPERVISOR COMMUNICATION IN TRAINING PROGRAM: AN EMPIRICAL STUDY IN MALAYSIA - Azman ISMAIL; Sofiah BONGOGOH; Sheela Chitra CHANDRA SEGARAN; Rodney GAVIN; Rabaah TUDIN (Management & Marketing)
A thorough review of human resource development literature shows that theability of supervisors to use good communication styles in managingprograms will invoke employees’ motivation to learn, this may lead toincreased positive individual attitudes and behaviors. The nature of thisrelationship is interesting, but little is known about the influence ofemployees’ motivation to learn in training management literature. Therefore,this study was conducted to examine the effect of supervisor communicationin training program and motivation to learn on individual attitudes andbehaviors using 100 usable questionnaires gathered from technicalemployees who have worked in one city based local authority in EastMalaysia (CLAEASTMALAYSIA). Outcomes of stepwise regression analysisshowed that relationship between motivation to learn and supervisorcommunication had been an important predictor of transfer of competencyand job performance. Statistically, this result confirms that motivation to learndoes act as a full mediating role in the training model of the in theorganizational sample. In addition, implications and limitations of the study,as well as directions future research are discussed.